2017
DOI: 10.1016/j.actamat.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

A 2-D nucleation-growth model of spheroidal graphite

Abstract: a b s t r a c tAnalysis of recent experimental investigations, in particular by transmission electron microscopy, suggests spheroidal graphite grows by 2-D nucleation of new graphite layers at the outer surface of the nodules. These layers spread over the surface along the prismatic direction of graphite which is the energetically preferred growth direction of graphite when the apparent growth direction of the nodules is along the basal direction of graphite. 2-D nucleation-growth models first developed for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…As illustrated in Figure 4a, spherical graphite particles consist of graphite grains radiating from the centre. Growth of the particle occurs in the direction of the crystal's C-axis where a new layer nucleates and grows on top of the next [24][25][26]. Protrusions, as shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure 4a, spherical graphite particles consist of graphite grains radiating from the centre. Growth of the particle occurs in the direction of the crystal's C-axis where a new layer nucleates and grows on top of the next [24][25][26]. Protrusions, as shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…When magnesium is added to cast iron melts, it first tights oxy gen and sulphur, and the remaining which is called free magnesium may adsorb freely on graphite [25 , 52] . While the overall or apparent growth direction of spheroidal graphite is along the basal plane direc tion, the growth mechanism involves carbon atoms attaching to the prismatic planes as previously discussed [56] . It has been suggested that spheroidizers adsorb on these prismatic planes [8 , 43 , 57] , and this has been accepted on the basis of laboratory studies on Fe C Ce alloys [27] .…”
Section: Discussionmentioning
confidence: 99%
“…9, where the adsorption energy of Bi and Pb has been set to that of Te ( Table A. Fig. 9 a good correlation between t:,. and Si, which stresses the importance of the size effect and the correlated number of outer electrons on the poisoning effectiveness of an element Finally, a schematic for spheroidal graphite degeneracy may be sug gested on the basis of the growth model previously developed [56]. This model assumes that growth of graphite spheroids proceeds by nucleation of new growth blocks at the outer surface of the spheroids which then grow along that surface, see Fig.…”
Section: Schematic Of Spheroidal Growth Of Graphite Following a 2d Numentioning
confidence: 96%
“…Further, it seems that this mechanism is the same for graphite precipitation from the melt and when encapsulated within austenite, either during the eutectic reaction or during solid-state cooling or heat-treatment in the austenite field [6,7]. In this line of thinking, it would be of interest to investigate the possibility of applying to solid-state growth the 2D nucleation and growth model previously developed for spheroidal graphite precipitation from the melt [28].…”
Section: This Observation Is Clearly Incompatible With Circumferentiamentioning
confidence: 99%